Temporal TCR dynamics and epitope diversity mark recovery in severe COVID-19 patients - Khare, Kriti; Yadav, Sunita; Halder, Sayanti; Ray, Yogiraj; Ganguly, Dipyaman; Pandey, Rajesh (Frontiers in Immunology, 2025)
IntroductionSevere COVID-19 is characterized by immune dysregulation, with T cells playing a central role in disease progression and recovery. However, the longitudinal dynamics of the T cell receptor (TCR) repertoire during the course of severe illness remain unclear.MethodsTo investigate temporal changes in adaptive immunity, we analyzed peripheral blood samples from the ICU-admitted severe COVID-19 patients (n = 36) collected at three time points: Day 1 (T1), Day 4 (T2), and Day 7 (T3). Bulk RNA-sequencing was performed to extract TCR repertoires, and cytokine profiles were assessed in parallel. TCR clonotypes were annotated using VDJdb and TCRex to infer potential epitope specificities.ResultsBy T3, we observed a 2.3-fold expansion in TCR clonotypes along with increased TCR-β (TRB) chain usage, indicating the emergence of a broad polyclonal T cell response. In contrast, TCR-γ (TRG) chain prevalence declined. Pro-inflammatory cytokines, including IL-1β and IL-6, were reduced over time, marking a shift toward immune resolution. Changes in CDR3 motifs and preferential TRBV gene segment usage were detected, suggesting repertoire adaptation. Additionally, annotated TCR clonotypes at T3 mapped to SARS-CoV-2 and other pathogen-associated epitopes (e.g., CMV, Plasmodium), reflecting possible cross-reactivity or memory T cell recruitment.DiscussionThese findings suggest a coordinated transition from immune dysfunction to recovery in severe COVID-19, marked by expanding TCR diversity, reduced inflammation, and predicted broadening of antigen recognition. The integrated analysis of TCR repertoire dynamics and cytokine profiles provides insights into the adaptive immune mechanisms underlying viral clearance and immune stabilization.